Macrocognition: From Theory to Toolbox - Klein, Gary; Wright, Corinne (Frontiers in Psychology, 2016)
We trace the evolution of field-based decision making models to the formation of the Naturalistic Decision Making (NDM) movement, to the expansion of NDM to model a range of macrocognitive processes and finally, the transition of those models into a set of methods and tools to boost cognitive performance.